Accumulation and health risk assessment of heavy metals in tissues of the shrimp and fish species from the Yumurtalik coast of Iskenderun Gulf, Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 2019)
In this study, concentrations of heavy metals were determined in the tissues of fish species (S. solea and S. aurata) and shrimp (P. semiaculatus) from the Yumurtalik zone of the Iskenderun Gulf, Turkey. The aim of of our study is to evaluate potential risks to human health associated with fish and shrimp consumption. Metals concentrations varied significantly depending on the tissues and species. The concentrations of Cu, Fe, Pb and Zn in fish and shrimp tissues were high, while Cd levels were relatively low. In comparing with the permissible limits set by the European Union and Food and Agricultural Organization for fish and shrimp, mean values of Cu, Fe, and Zn were within acceptable limits, but the mean values of Cd and Pb exceeded the limits. From the standpoint of human health, this study suggests that the observed Pb and Cd accumulation may pose a possible health risk to excessive S. solea and P. Semiculatus consumers in Turkey.
Keywords: Environmental hazard; Environmental health; Environmental pollution; Environmental risk assessment; Environmental toxicology; Food science; Food safety; Heavy metals; Fish; Shrimp; Risk assessment; Iskenderun Gulf; Mediterranean Sea; MULLUS-BARBATUS; MUGIL-CEPHALUS; WATER